Homogeneous Components of a CDH Fuzzy Space - Samer Al Ghour (Institute of Advanced Engineering and Science, 2019)
We prove that fuzzy homogeneous components of a CDH fuzzy topological space (X,T) are clopen and also they are CDH topological subspaces of its 0-cut topological space (X,T0).